Active cytomegalovirus infection diagnosed by real-time PCR in patients with inflammatory bowel disease: a prospective, controlled observational study*. (1st September 2016) - Thörn, Mari; Rorsman, Fredrik; Rönnblom, Anders; Sangfelt, Per; Wanders, Alkwin; Eriksson, Britt-Marie; Bondeson, Kåre
Abstract: Objective: It is assumed that cytomegaloviral (CMV) infection in inflammatory bowel disease (IBD) is caused by reactivation due to the immunosuppressive therapy, but the role of CMV as a pathophysiological factor and prognostic marker in IBD is unclear. The aim of this study was to investigate CMV infection in IBD, with real-time polymerase chain reaction (PCR) and immunohistochemistry, with emphasis on newly diagnosed disease. Materials and methods: In this prospective, controlled study, 67 patients with IBD and 34 control patients with irritable bowel syndrome (IBS) or rectal bleeding were included. Serology for CMV was analysed along with CMV DNA in plasma, mucosal biopsies, and faeces. Mucosal biopsies were further analysed with histopathology and CMV immunohistochemistry. Results: Detection of CMV IgM was more common in patients with IBD, compared to controls, 21% versus 3%. CMV DNA was found in 16% of patients with newly diagnosed, untreated IBD and in 38% of steroid-treated patients. Four of the five patients that needed urgent surgery were CMV-DNA positive in at least one of three sample types. None of the controls had detectable CMV DNA. Conclusions: Active CMV infection was found in high proportions of newly diagnosed untreated patients with IBD, in patients on immunosuppression and in patients in the need of surgery. Low CMV-DNA levels in non-immunosuppressed patients were not a risk factor for the development of more severe IBD, while the detection of CMV DNA in patients on immunosuppressive therapy may foresee disease progression.